Identification of B‐cell dominant epitopes in the recombinant protein P29 from Echinococcus granulosus. Issue 5 (19th April 2022) - Lv, Yongxue; Li, Shasha; Zhang, Tingrui; Zhu, Yazhou; Tao, Jia; Yang, Jihui; Chang, Liangliang; Wu, Changyou; Zhao, Wei
Abstract: Introduction: Echinococcus granulosus ( E .  granulosus ) causes a hazardous zoonotic parasitic disease. This parasite can occupy the liver and several areas of the body, causing incurable damage. Our previous studies have provided evidence that the recombinant protein P29 ( rEg.P29 ) exhibit immune protection in sheep and mice against pathological damage induced by E. granulosus, showing its potential as candidate for vaccine development. However, information on the B‐cell epitopes of rEg.P29 has not yet been reported. Methods: Immunological model was established in mice with rEg.P29 . SDS‐PAGE and Western blot were used to identify protein. Screening for B‐cell dominant epitope peptides of rEg.P29 by enzyme‐linked immunosorbent assay (ELISA) and immune serum. Dominant epitopes were validated using ELISA and flow cytometry. Multiple sequence alignment analysis was performed using BLAST and UniProt. Results: Immunization with rEg.P29 induced intense and persistent antibody responses, and the epitope of the dominant antigen of B cells are identified as rEg.P29 166–185 (LKNAKTAEQKAKWEAEVRKD). Anti‐ rEg.P29 166–185 ‐specific antibodies lack epitopes against IgA, IgE, and IgG3, compared to anti‐ rEg.P29 ‐specific antibodies. However, anti‐ rEg.P29 166–185 IgG showed comparatively higher titers, as determined among those peptides by endpoint titration. In addition, rEg.P29 and rEg.P29 166–185 promote B‐cell activation and proliferation in vitro. The dominant epitopes are relatively conserved in different subtypes of the rEg.P29 sequence. Conclusion: rEg.P29 166–185 can act as a dominant B‐cell epitope for rEg.P29 and promote cell activation and proliferation in the same way as rEg.P29 . Abstract : Our study provides information for the study of rEg.P29 peptide vaccines and sheds light on the rational design of vaccines.